Perbandingan Tingkat Kompetensi Karyawan Salon Kecantikan Lulusan SMK Tata Kecantikan dengan Lulusan SM/SMK Non Kecantikan di Kota Padang - Wira Meswari, Sisi Yulia; Rahmiati, Rahmiati; Rosalina, Linda (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This study base on a different competence between attitude and psychomotor off the employee off beauty salon graduates from vocational and non beauty education. This study aimed to analyze to the compane the competence and psychomotor off the employee. This is a descriptive quantitative and comparative research. The population are three beauty salons with 39 total employes samples, with total sampling techniques. Data is analysed by a percentage formula, proving competency gap using a subset of the statistics test with t-test independent with the type of Pooled Variance. Results of the study in vocational employees are 67.88%with affective and 71.80% with psychomotor. For the non vocational, affective 72.09%, and 62.17%psychomotor. The t test analisis on behavioral competences result in bigger table’s t than counted t (1,137 <2,021), wich means no difference with significancy at 5%(0,05). Different result is showed in psychomotor competence, table’ t is smaller than counted t (2,540> 2,021), wich means there is a difference between the vocational graduated and non vocational graduated employee with significancy at 5%(0,05).Keywords: Comparison of competence, affective, psychomotor, beauty salon